The Role of Aire, microRNAs and Cell-Cell Interactions on Thymic Architecture and Induction of Tolerance - Geraldo Aleixo Passos (Frontiers Research Topics, 2016)
The focus of this eBook is to bring new insights into central immune tolerance. To fulfill that, much has been discussed about the master in the regulation of tolerance, the autoimmune regulator (Aire) gene the main thymus cell type that expresses this gene, the medullary thymic epithelial cells (mTECs). It includes one Editorial and 12 other excellent contributions in the format of mini reviews or original research papers covering one or more of these aspects: promiscuous gene expression (PGE), epigenetics, miRNAs, association of the Aire gene and miRNAs, thymocyte-TEC interaction, coxsackievirus and type 1 diabetes, exosomes in the thymus, thymic crosstalk, thymic B cells, T cell development, chemokines and migration of T cells, miRNAs and the thymic atrophy, cell-cell interactions, and thymus ontogeny. Authors raised hypothesis, discuss concepts, and show open questions. The remaining important issues to resolve questions within the central tolerance research are briefly discussed below.